2015
DOI: 10.1038/ncomms10079
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction in light–oxygen–voltage receptors lacking the adduct-forming cysteine residue

Abstract: Light–oxygen–voltage (LOV) receptors sense blue light through the photochemical generation of a covalent adduct between a flavin-nucleotide chromophore and a strictly conserved cysteine residue. Here we show that, after cysteine removal, the circadian-clock LOV-protein Vivid still undergoes light-induced dimerization and signalling because of flavin photoreduction to the neutral semiquinone (NSQ). Similarly, photoreduction of the engineered LOV histidine kinase YF1 to the NSQ modulates activity and downstream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
179
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(201 citation statements)
references
References 55 publications
(132 reference statements)
16
179
6
Order By: Relevance
“…Next, we assessed the response to intensity and pulse frequency of illumination in pDusk and pDawn systems harboring YF1 variants that lacked the conserved adduct‐forming Cys62 inside the LOV photosensor (Figures and S2). We previously showed that such cysteine‐devoid LOV receptors could still retain light sensitivity and downstream signal transduction because, in the absence of the conserved cysteine, blue‐light absorption promotes reduction of the flavin chromophore to the neutral semiquinone state (NSQ) . Notably, formation of the NSQ entails protonation of the flavin N5 atom, which is key to triggering downstream responses.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Next, we assessed the response to intensity and pulse frequency of illumination in pDusk and pDawn systems harboring YF1 variants that lacked the conserved adduct‐forming Cys62 inside the LOV photosensor (Figures and S2). We previously showed that such cysteine‐devoid LOV receptors could still retain light sensitivity and downstream signal transduction because, in the absence of the conserved cysteine, blue‐light absorption promotes reduction of the flavin chromophore to the neutral semiquinone state (NSQ) . Notably, formation of the NSQ entails protonation of the flavin N5 atom, which is key to triggering downstream responses.…”
Section: Resultssupporting
confidence: 90%
“…Concomitant with thioether formation, the N5 atom of the flavin chromophore is protonated, which triggers hydrogen‐bond rearrangements throughout the LOV photosensor. Studies on cysteine‐devoid variants of LOV receptors revealed that N5 protonation was both necessary and sufficient for downstream signal propagation . The stability of the thioether bond in cysteine‐containing LOV receptors is strongly governed by temperature, solvent composition, and molecular environment of the flavin chromophore .…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study a VVD variant in which the active site Cys has been changed to Ala was also found to signal after photoreduction of the flavin to the neutral semiquinone state, which also has N5 protonated. 19 In our simulations the Cys-less variant also gives rise to the Gln conformational switch and thus points to a similar conformational activation mechanism in the Cys-less variant. Finally, free energy simulations indicate that in the light state the barrier for Gln182 flipping is reduced and the flipped conformation is substantially stabilized.…”
Section: Introductionsupporting
confidence: 68%
“…1, A and B). Such behavior suggests that the oxidation potential of the FMN cofactor may reside within physiologically relevant ranges as has been observed previously in LOV protein variants (18,34) and has recently been shown of being competent for signal transduction (35). Thus, ENV1 may employ the semiquinone in dark state signaling.…”
Section: Resultsmentioning
confidence: 72%